Epidemiology of Carbapenemase-Producing Enterobacteriaceae and Acinetobacter baumannii in Mediterranean Countries. (13th May 2014) - Djahmi, Nassima; Dunyach-Remy, Catherine; Pantel, Alix; Dekhil, Mazouz; Sotto, Albert; Lavigne, Jean-Philippe
Abstract : The emergence and global spread of carbapenemase-producing Enterobacteriaceae and Acinetobacter baumannii are of great concern to health services worldwide. These β -lactamases hydrolyse almost all β -lactams, are plasmid-encoded, and are easily transferable among bacterial species. They are mostly of the KPC, VIM, IMP, NDM, and OXA-48 types. Their current extensive spread worldwide in Enterobacteriaceae is an important source of concern. Infections caused by these bacteria have limited treatment options and have been associated with high mortality rates. Carbapenemase producers are mainly identified among Klebsiella pneumoniae, Escherichia coli, and A. baumannii and still mostly in hospital settings and rarely in the community. The Mediterranean region is of interest due to a great diversity and population mixing. The prevalence of carbapenemases is particularly high, with this area constituting one of the most important reservoirs. The types of carbapenemase vary among countries, partially depending on the population exchange relationship between the regions and the possible reservoirs of each carbapenemase. This review described the epidemiology of carbapenemases produced by enterobacteria and A. baumannii in this part of the world highlighting the worrisome situation and the need to screen and detect these enzymes to prevent and control their dissemination.